The role of the school principal in developing the leadership skills of the students of the secondary school for boys in Riyadh city - Al - Thibiani, Ahmed Hassan (Journal of Educational and Psychological Sciences, 2018)
The aim of the study is to identify the role of the school principal in developing leadership skills (innovation, decision-making, responsibility) among high school students from the principals’ point of view. The research will also reveal the obstacles that the school principal plays in developing the leadership skills of school students Secondary education. To achieve the objectives of the study, the researcher followed the descriptive descriptive method, through the application of the study tool (questionnaire) to the whole community of the study, which included all managers of the secondary schools in Riyadh, (139) managers. The questionnaire consisted of (32) words distributed on two axes: the role of the school principal in developing the leadership skills of secondary school students, while the second topic dealt with the obstacles that the school principal played in the development of leadership skills among high school students. The role of the school principal in the development of leadership skills among high school students came at a "high" level, where the role of the school principal in developing the skill of responsibility comes first, followed by the role of the school principal in developing the skill of innovation and innovation. Al-Qara T. In addition, the obstacles to the development of leadership skills among high school students were "high." The study recommended that the institutions of the community be closely linked with the school. The director delegated some of his powers to the administrative staff to enable him to perform some of the tasks entrusted to him. The supervisors of education with leadership skills, how to discover and develop them among the students, and the importance of the attention of those who prepare the school curriculum with leadership culture.